Identifying and Validating Components of Decision-Making of the Secondary School Pricniplals in Iranian Eeducation System - Hasan Fazeli; Abbas Abbaspour; Hamid Rahimian; Ali Delavar (پژوهش در نظام‌های آموزشی, 2021)
The aim of this study was to identify the dimensions and components of administrators decision making in educational organization. This research method was a mixed exploratory research. The statistical population in the qualitative section included all school principals in Tehran and expert principals of educational system and the sampling method was purposeful and theoretical. In quantitative part, the statistical population was all school principals in Tehran, which according to Cochran's formula, the number of sample members was 249. Data collection tool in the qualitative part of the interview was semi-structured and retesting and reliability between the two coders were used to check the validity and reliability of the interviews and coding, and they are approved as 0.75 and 0.77 respectively. The collection tool in the quantitative part was a researcher-made questionnaire that its validity was checked and confirmed by content validity method and confirmatory factor analysis. The reliability of the instrument was evaluated and confirmed using Cronbach's alpha method, and it was approved as 0.625. Grounded theory approach was used to analyze the data in the qualitative part. One-sample t-test, Pearson correlation coefficient and confirmatory factor analysis were used to analyze the quantitative part. The findings showed: 1- Dimensions of decision making were classified into eight categories: knowledge, experience and expertise, ethical, psychological, social, human, technical and economic. 2- There was a significant correlation between the dimensions and components. 3- Knowledge dimension and psychological dimension had the highest and lowest mean, respectively.